2021
DOI: 10.3390/ma14010212
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Lubricant Dose on the Reduction of Wear Dies Used in the Forging Process of the Valve Forging

Abstract: The paper presents the results of research on the influence of the settings of lubrication and cooling system parameters (solenoid valve opening time and lubricant feed pressure in terms of its quantity) in order to select the optimal lubricating conditions and thus reduce the wear of the dies used in the first forging operation of the valve forging made of high-nickel steel. Based on the observation of lubrication in the industrial process, it was found that a significant part of the lubricant fails to reach … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…These suggest improper settings of the lubrication-cooling system (Figure 5). And so, we can conclude about significant possibilities, if not a necessity, to optimize the analyzed technology [33]. Based on the conducted analysis, we can observe that the average durability of the punches in the selected time period equals about 1150 forgings, where we should note the high value of standard deviation.…”
Section: Analysis Of Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…These suggest improper settings of the lubrication-cooling system (Figure 5). And so, we can conclude about significant possibilities, if not a necessity, to optimize the analyzed technology [33]. Based on the conducted analysis, we can observe that the average durability of the punches in the selected time period equals about 1150 forgings, where we should note the high value of standard deviation.…”
Section: Analysis Of Resultsmentioning
confidence: 81%
“…These suggest improper settings of the lubrication-cooling system (Figure 5). And so, we can conclude about significant possibilities, if not a necessity, to optimize the analyzed technology [33].…”
Section: Analysis Of Resultsmentioning
confidence: 95%
“…Moreover, the lubrication conditions were altered through slight dilution of the lubricant and reduced lubricant doses. Therefore, in the industrial forging process, intensive research and tests have been carried out using a fully automatic cooling and lubricating device developed by the authors, which has been successfully used during forging on presses [42][43][44], where there are much lower mechanical drag values, than when hammering is the case.…”
Section: Changes and Improvements To The Current Technologymentioning
confidence: 99%
“…In the event of a downtime or technological break, the tools are reheated and the temperature of the tools is measured with a pyrometer before the process is started again. In the industrial forging process for lubrication, a fully automatic cooling and lubricating device developed by the authors was used, which was demonstrated in several studies [34][35][36]. Such devices ensure stable and repeatable lubrication conditions.…”
Section: Analysis Of Industrial Forging Processmentioning
confidence: 99%